Digital photography in orthodontics - Kumar Shetty B, Sharath; Kumar Y, Mahesh; Sreekumar, Chandrima (International Journal of Dental Research, 2017)
The buzzword today is digital. Be it music, T.V., video, watch, diary or any appliance. The world is going digital. Film less photography, pictures on a chip, call it what, this is a new phenomenon of technology. It is big, and it is the way things will be from this day forwards. For over 160 years, photography has been based on the silver halide film, which is now being replaced. Digital photography has come about as a result of convergence of both IT and photography. And it has so much to offer us. This article reviews the possibilities of digital photography in orthodontics.